(untitled) (Fiep Bulletin - online, 2015)
In the current society many professions suffer influence from labor stress because of the great pressures to increase productivity, effectiveness and time reduction in accomplishment of tasks. Bank clerks have been one of the professional categories more affected by stress, together with police officer and primary school teacher. Studies indicate that stress perception can be influenced by life style, been the actives less committed by stress. This research aimed to verify how workers of a state bank in Florianópolis/SC, identified as sedentary and active life stile, perceive their stress. The sample was composed by 45 females bank clerks, 12 active and 33 sedentary. The instrument used for data’s collection was the Perceived Stress Scale developed by Cohen et al. (1983) and adapted by Ururahy (1997). The habitual physical activities was investigated by a questionnaire developed by Pate and adaptaded by Nahas (2001). The data had been treated by descriptive statistics and inference (t test). Among the variables related to stress, anxiety was the higher level (2,58 s=0,86), where sedentary women demonstrated a higher anxiety level related to active (p<0,05). However, active had demonstrated greater competitiveness and difficulty in expressing their feelings. The variable more positively associated to stress was tension and aggressiveness. The sedentary bank clerks had presented perceived stress index (IPS) of 25,64 (s=7.02/-8, +42), while the active had lower IPS (24,25; s=8,11/-11, +37), without significant difference (p>0,05). This way, it was concluded that life style can not determine the perceived stress in bank clerks, suggesting that the other variables that influence stress, specially in the pressure situation lived by the bank clerks can be influenced on their ISP, decreasing the benefits of an active life style.